Depressive-Type Schizoaffective Disorder in a Young Adult Woman: Challenges in Diagnosis and Management, A Case Report - Muhammad Akmal Ghani; Tendry Septa; Risti Graharti (CV. Jasa Sukses Abadi, 2026)
Depressive-type schizoaffective disorder (F25.1) is a psychiatric disorder characterized by the coexistence of psychotic symptoms typical of schizophrenia and prominent depressive symptoms within the same episode of illness. This disorder is thought to involve dysregulation of multiple neurotransmitter systems, particularly dopamine and serotonin, which contribute to the simultaneous manifestation of psychotic and affective symptoms. Establishing the diagnosis remains challenging due to its overlapping clinical features with schizophrenia and major depressive disorder with psychotic features. This case report describes a 26-year-old woman who presented to the Psychiatric Outpatient Clinic of Lampung Provincial Mental Hospital with complaints of talking to herself, auditory hallucinations consisting of voices commenting on her daily activities, insomnia, anxiety, feelings of worthlessness, and suicidal ideation that emerged during the course of her illness. The symptoms developed following psychosocial stressors, including family conflicts and economic difficulties. Mental status examination revealed hypotymic mood, blunted affect, circumstantial thought process, and a history of persistent auditory hallucinations, while cognitive function, orientation, and memory remained intact. Based on psychiatric assessment and the diagnostic criteria of the Indonesian Classification of Mental Disorders (PPDGJ-III), the patient was diagnosed with depressive-type schizoaffective disorder (F25.1). The diagnosis was established due to the simultaneous presence of schizophrenic and depressive symptoms within the same episode of illness. Differential diagnoses considered included paranoid schizophrenia and severe depressive episode with psychotic symptoms. The patient received pharmacological treatment consisting of risperidone, trihexyphenidyl, fluoxetine, lithium carbonate, and clobazam, accompanied by psychoeducation and supportive psychotherapy. Clinical improvement in psychotic symptoms and overall functioning was observed following treatment. Depressive-type schizoaffective disorder requires comprehensive clinical evaluation to distinguish it from other psychotic and affective disorders and necessitates a multidisciplinary approach combining pharmacological and psychosocial interventions to improve patient outcomes.